Pneumococci can persistently colonize adult patients with chronic respiratory disease. - Domenech, A; Ardanuy, C; Balsalobre, L; Marti, S; Calatayud, L; De la Campa, A; Brueggemann, A; Liñares, J (2012)
Streptococcus pneumoniae plays an important role in causing acute exacerbations in patients with chronic respiratory disease. However, few data are available regarding pneumococcal persistence in adult patients with chronic respiratory diseases. Fifty pneumococci recovered from sputum samples (1995 to 2010) from 13 adult patients with ≥ 3 episodes of acute exacerbation or pneumonia, with the same serotype and pulsed-field gel electrophoresis (PFGE) pattern, were studied. Multilocus sequence typing (MLST) loci, penicillin-binding protein (PBP) genes (pbp2x, pbp1a, pbp2b), and the quinolone-resistant determining regions (QRDRs) of parC, parE, and gyrA were PCR amplified and sequenced. The average time between the first and last episode was 582 days (standard deviation [SD], ± 362). All but two patients received multiple courses of β-lactam treatment, and all persistent strains were resistant to penicillin; however, the PBP sequences were stable over time apart from one variable nucleotide in pbp2x, observed among pneumococci isolated from three patients. In contrast, 7/11 patients treated with fluoroquinolones had fluoroquinolone-resistant pneumococci. In three patients, the initially fluoroquinolone-susceptible strain developed resistance after fluoroquinolone therapy, and in the remaining four patients, the persistent strain was fluoroquinolone resistant from the first episode. QRDR changes involved in fluoroquinolone resistance were frequently observed in persistent strains after fluoroquinolone treatment; however, the PBP sequences and MLST genotypes of these strains were stable over time.